Sistem pemerintahan kerajaan Jawa klasik - Purwadi, 1971-; Siyo, Kasim; Soekirman; Hariwijaya, M. (Medan, Sumatera Utara : Pujakesuma, 2007)
History of Javanese kingdoms and their system of government
Daftar pustaka : p. 623-630
Keywords: Java (Indonesia) -- History; Java (Indonesia) -- Politics and government